(untitled) (Global Journal of Human-Social Science, 2015)
Providing health and education services in the rural areas is one of the biggest challenge that is faced by the government of India. With nearly 70 per cent population living in rural areas have less number of health and education services than their urban counterpart. Health care and education amenities are hardly available in the rural areas, and this is the core reason for migration of the rural people to urban areas. This paper focuses on the distribution of health and education services in the rural areas of Aligarh district taken primary and secondary data under consideration. Methodological principle adopted for the present study is cumulative frequency distribution, mean spacing, Gini’s coefficient concentration ratio, and graphical representation of the cumulative frequency curve. Result shows that there is gap in the availability of health and education services in the rural areas in different population size group of settlements.